Development of micropropagation system for yam (Dioscorea spp.) using somatic embryogenesis - Ossai, C.; Balogun, M.; Maroya, N.; Asiedu, Robert (International Institute of Tropical Agriculture, 2018)
Inadequate availability of disease-free planting materials remains a major constraint to yam production. The tissue culture technique has been used to regenerate disease-free plantlets from pre-formed, heattreated meristems followed by micropropagation. This procedure, however, has a low multiplication ratio with an average of 1: 4 every eight weeks. Embryo production from somatic cells (somatic embryogenesis, SE) is a system in which each somatic cell can regenerate a complete plantlet. However, previous reports show low SE induction frequencies and significant variations in success rates among different genotypes while hardly any report exist for improved varieties that farmers desire, especially in Nigeria. Studies were carried out to evaluate the effects of different plant growth regulators (PGRs) on induction of somatic embryogenesis of the following genotypes: one improved Dioscorea alata (TDa 291) and three improved (TDr 95/19177, TDr 89/2665, TDr 95/18544) and one landrace (Obioturugo) of Dioscorea rotundata. Leaf, stem, and axillary bud explants were cultured in MS basal medium containing fifteen treatment combinations of 2,4-Dichlorophenoxyacetic acid (2,4-D), Naphthaleneacetic acid (NAA), Benzylaminopurine (BAP), Picloram, and Uniconazole-P (UP). The genotype TDr 95/19177 was tested for SE in Temorary Immersion Bioreactor System (TIBS). The incidence of induction of callus formation and plantlet regeneration from the three explants were recorded. Embryogenic callus induction was highest (87%) from axillary buds cultured on modified MS + 2 mg/l of 2,4-D + 1 mg/l of NAA while 1 mg/l of BAP + 9. 9 mg/l of UP had the highest percentage plantlet regeneration of 50% in TDr 95/18544 and an average of 37% across genotypes at a mean of 5 plantlets per explant. The genotype TDr 95/19177 was successfully regenerated via indirect somatic embryogenesis in the SETIS Type Temporary Immersion Bioreactor System.